Detail-preserving exposure fusion using subband architecture - Shen, Jianbing (2013)
In this paper, we present a novel detail-preserving fusion approach from multiple exposure images using subband architecture. Given a sequence of different exposures, the Quadrature Mirror Filter (QMF) based subband architecture is first employed to decompose the original sequence into different frequency subbands. After that, we compute the importance weight maps according to the image appearance measurements, such as exposure, contrast, and saturation. In order to preserve the details of the subband signals, we compute the gain control maps and improve these subbands. Finally, the coefficients of subbands are blended into a high-quality detail-preserving fusion image. Experimental results demonstrate that the proposed approach successfully creates a visually pleasing exposure fusion image.